A Study of a Nonlinear Ordinary Differential Equation in Modular Function Spaces Endowed with a Graph - Jaauad Jeddi; Mustapha Kabil; Samih Lazaiz (Journal of Function Spaces)
In this paper, we prove by means of a fixed-point theorem an existence result of the Cauchy problem associated to an ordinary differential equation in modular function spaces endowed with a reflexive convex digraph.